Measurement and Management of University Social Responsibility: Methodological Advances and Challenges for Institutional Sustainability - Salguero, James Carlos Fernández; Duche-Pérez, Aleixandre Brian; Ugarte, Cesar Alejandro Del Carpio; Castillo, Alison Serruto (Journal of Cultural Analysis and Social Change, 2025)
In recent decades, university social responsibility (USR) has become a strategic dimension of higher education, closely linked to institutional sustainability and to universities’ commitment to addressing social, territorial, and environmental challenges framed by the 2030 Agenda. Despite its growing relevance, the measurement and management of USR remain characterized by significant conceptual and methodological heterogeneity, which constrains cross-institutional comparability and limits the effective use of evaluation results in decision-making processes. The aim of this article is to critically analyze recent methodological advances in the measurement of USR and to examine the challenges these approaches pose for sustainable university management. To this end, a documentary study with an analytical–critical and descriptive approach was conducted, based on a theoretical–methodological review of indexed scientific literature published between 2017 and 2025. The analysis identifies three dominant methodological trends: quantitative approaches focused on indicators and perceptual instruments; qualitative and participatory approaches oriented toward stakeholder engagement; and hybrid models that integrate measurement, explanation, and impact assessment through innovative tools such as evaluative matrices and explanatory modeling techniques. The findings show significant progress in capturing perceptions, processes, and social impacts associated with USR, while also revealing persistent limitations related to standardization, validity, and the weak linkage between evaluation and institutional management. It is concluded that strengthening USR requires comprehensive and participatory measurement systems oriented toward decision-making, capable of effectively connecting evaluation processes with university governance and long-term institutional sustainability.